ANALISIS PENGGUNAAN PREPOSISIâ€œDUIâ€ DAN â€œDUIYUâ€ PADA MAHASISWAPRODI BAHASA MANDARIN UNTAN - Katherina, Miss; Thamrin, Lily; Lusi, Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractPreposition word is one of the very important elements in mandarin Â language teaching and learning. One of the preposition wordthat is very common being used in chinese language is â€œduiâ€ and â€œduiyuâ€. When students learn these two words theyare often confused, so they found a lot of problem in using these two words. To measure the ability of the using condition and difficult point of the students of University of Tanjungpura Chinese Language Major Batch 2015 in usingâ€œduiâ€ and â€œduiyuâ€. The researcher used literature study as the method to collect data. The test results have show towards indicate that the total percentages of the studentsâ€™ accuracy in the part one about â€œduiâ€ is 54% (class A) and 65% (class B), the studentsâ€™ accuracy in the part two about â€œduiâ€ is 32% (class A) and 64% (class B). The total percentages of the studentsâ€™ accuracy in the part one about â€œduiyuâ€ is 40% (class A) and 44% (class B) and part two about â€œduiyuâ€ is 10% (class A) and 37% (class B). In conclusion, the results show have the studentsâ€™Â the using condition of the word â€œduiâ€is better than the word â€œduiyuâ€ and total the percentage also showed that students in class B got higher ability than students in class A.Keywords: preposition wordÂ â€œduiâ€Â Â Â â€œduiyuâ€Â Â Using analysis